Odpowiedź :
1.
0,5x * 70% = 0,5x * 0,7 = 0,35x
2.
(-2+1)(-4-4)= (-1)(-8)= 8
4.
2y2x - ( 4y2x +3yx2) + 3x2y=
2y2x - 4y2x - 3x2y + 3x2y=
=-2y2z
0,5x * 70% = 0,5x * 0,7 = 0,35x
2.
(-2+1)(-4-4)= (-1)(-8)= 8
4.
2y2x - ( 4y2x +3yx2) + 3x2y=
2y2x - 4y2x - 3x2y + 3x2y=
=-2y2z
1. ½x pomnożone przez 0,3
2.(x+1)(2x-4)= 2x²-4x+2x-4=2x²-2x-4
2x²-2x-4=2*(-2)²-2-(-2)-4=4-2-4=(-2)
3.
180⁰-20⁰-2'alfa'=180⁰
160⁰-2 'alfa'=180⁰
?
4.2y2x – (4y * xy + 3yx2) + 12x2y2 =4xy (4xy²+6xy) +48xy= 16x²y³+24x²y²+48xy
mam nadzieję, że chociaż trochę pomogłam :)
2.(x+1)(2x-4)= 2x²-4x+2x-4=2x²-2x-4
2x²-2x-4=2*(-2)²-2-(-2)-4=4-2-4=(-2)
3.
180⁰-20⁰-2'alfa'=180⁰
160⁰-2 'alfa'=180⁰
?
4.2y2x – (4y * xy + 3yx2) + 12x2y2 =4xy (4xy²+6xy) +48xy= 16x²y³+24x²y²+48xy
mam nadzieję, że chociaż trochę pomogłam :)